Representation Of Freedom As An Embodiment Of The Spirit Of Nationalism For Students Of Sman 1 Kandangan Kediri District - Naja, Anang Darun; Suhaimi, Imam (Literacy: Journal of Education and Social Science, 2024)
Therefore, this study aims to analyze and describe the representation of freedom as a manifestation of the nationalist spirit of the SMAN 1 Kandangan Kediri District. The qualitative approach will be used as an approach in this study, involving students, homerooms teacher, and principals in the SMAN 1 Kandangan Kediri District as informants. Data analysis will be carried out according to the qualitative stages as determined qualitatively by three stages of analysis according to the Miles & Huberman model. The results obtained in this study are that the majority of Bengkulu Grakarsa Vocational School students have understood the concept of freedom in accordance with the laws and regulations, while others still have an incorrect understanding. The phenomena encountered by students will shape students' thoughts and attitudes, including negative phenomena in the form of abuse of freedom by government officials. Therefore, efforts are needed from the government to discipline its officials to carry out their duties with full discipline and compliance with statutory regulations. This will be used as an example and practical educational material that forms students' understanding of the concept of freedom in accordance with statutory regulations. The study examines the nationalist ideals of the millennial generation using Kartodirdja's theory, and discovers that when their nationalist spirit dwindles, attempts are made to strengthen it.